Legitimizing Sexism: Critical Discourse Analysis on Sexism in a Political U.S. Podcast - Sohlman, Katri (My University, 2023)
Sexism in media and in politics is not a new phenomenon, yet the current U.S. political landscape and new forms of media, such as podcasts, demand the issue to be researched further. In this thesis, I analyze the sexist language used in a The Ben Shapiro Show podcast episode. Research questions explore what kind of sexist language is used and how sexism is legitimatized in the podcast. Additionally, the impact of sexist discourses on the podcast’s audience’s attitudes and stances is discussed. The analysis is based on Critical Discourse Analysis, focusing on especially its feminist branches as well as the Foucauldian understanding of power. Works of Michelle Lazar, Sarah Mills, and Alice Freed are used to form a base for sexism analysis. The legitimation analysis is completed by basing it on Theo Van Leeuwen’s Social Actors Approach and legitimization theory and realized via M.A.K Halliday’s transitivity analysis. The analysis shows that the most used type of sexism is overt sexism and that legitimations via authorization and evaluation are used equally. The results suggest that sexist language is utilized in right-wing conservative media to limit women’s participation in politics. Sexist attitudes are fostered and naturalized via podcasts and a podcaster creates a community from their audience which trusts the information spread by the podcaster. The study on sexism in podcasts adds to the research on sexist language in media. As podcasts have a unique position in the field of media, located somewhere between traditional and social media, the current study provides a unique point of view on media sexism and sexism in politics.
Keywords: sexism, Critical Discourse Analysis, legitimation, podcast, sexist language, overt sexism, covert sexism